J. R. R. Tolkien: The Philosophical Basis of Sub-Creative Words. - MENTXAKATORRE ODRIOZOLA, JON (Logos: A Journal of Catholic Thought & Culture)
The article offers information on J.R.R. Tolkien, writer's stories in Middle-earth that differentiate them from other fictional stories as their inspiration. It focuses on writer's study of languages simply and plainly for the intense aesthetic pleasure. It focuses on the use of a personal aesthetic language with the history of Western literature after primordial creative act.